1997
DOI: 10.1007/s002709900185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Directional Atherectomy Studied by Intravascular Ultrasound in Femoropopliteal Artery Stenosis

Abstract: Lumen enlargement following DA is predominantly due to plaque excision. Vessel expansion combined with plaque excision varies in different stenoses and is an important factor in eccentric and soft lesions. Despite additional DA considerable plaque remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[12][13][14][15][16] IVUS also enhances sensitivity for detecting procedural complications, including arterial dissections. [17][18][19][20][21][22] This may result in important changes to the treatment plan to minimize short-term peri-procedural complications. This systematic review also found that IVUS is an effective tool in diagnosing, characterizing, and evaluating iliofemoral venous disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16] IVUS also enhances sensitivity for detecting procedural complications, including arterial dissections. [17][18][19][20][21][22] This may result in important changes to the treatment plan to minimize short-term peri-procedural complications. This systematic review also found that IVUS is an effective tool in diagnosing, characterizing, and evaluating iliofemoral venous disease.…”
Section: Discussionmentioning
confidence: 99%
“…12 16 IVUS also enhances sensitivity for detecting procedural complications, including arterial dissections. 17 22 This may result in important changes to the treatment plan to minimize short-term peri-procedural complications.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to PTA and stent implantation, they offer the theoretical advantages of eliminating stretch injury on arterial walls, limiting acute dissection (and the need for adjunctive stenting), and reducing elastic recoil, thereby potentially reducing the rate of restenosis. Historically, however, neither rotational nor directional atherectomy, whether used alone or with adjunctive PTA, has shown any significant long-term benefit over PTA alone in coronary or peripheral arteries, 12,2837 despite promising results in some single-center studies. 38…”
Section: History Of Atherectomy In the Coronary And Infrainguinal Arteriesmentioning
confidence: 99%
“…The theoretical advantages of atherectomy notwithstanding, a large amount of retained plaque was reported in a randomized trial of the Simpson device. 35 Despite numerous advances in cutter design or size of the Simpson catheter or other directional atherectomy devices, there was no documentation of any treatment success compared to the less expensive and simpler angioplasty balloons. Thus, atherectomy never gained acceptance as a primary method of treatment for PAD.…”
Section: History Of Atherectomy In the Coronary And Infrainguinal Arteriesmentioning
confidence: 99%
“…Despite any superior efficacy over only angioplasty alone in the coronary vasculature, there remains an interest in atherectomy for use in the peripheral vascular space. Given that current angioplasty and stenting data have not shown as much long‐term success, there is a growing interest in alternative athero‐ablative technologies 7–17 . The peripheral arteries, in particular the infra‐inguinal territory, undergo many dynamic forces that make translation of the coronary interventional literature to the peripheral vasculature not as relevant.…”
Section: Introductionmentioning
confidence: 99%